Echinococcus granulosus ubiquitin-conjugating enzymes (E2D2 and E2N) promote the formation of liver fibrosis in TGFβ1-induced LX-2 cells - Du, Xiaodi; Hua, Ruiqi; He, Xue; Hou, Wei; Li, Shengqiong; Yang, Aiguo; Yang, Guangyou (Parasites & vectors, 2024)
Cystic echinococcosis (CE) is a widespread zoonosis caused by the infection with Echinococcus granulosus sensu lato (E. granulosus s.l.). CE cysts mainly develop in the liver of intermediate hosts, characterized by the fibrotic tissue that separates host organ from parasite. However, precise mechanism underlying the formation of fibrotic tissue in CE remains unclear. To investigate the potential impact of ubiquitin-conjugating enzymes on liver fibrosis formation in CE, two members of ubiquitin-conjugating (UBC) enzyme of Echinococcus granulosus (EgE2D2 and EgE2N) were recombinantly expressed in Escherichia coli and analyzed for bioinformatics, immunogenicity, localization, and enzyme activity. In addition, the secretory pathway and their effects on the formation of liver fibrosis were also explored. Both rEgE2D2 and rEgE2N possess intact UBC domains and active sites, exhibiting classical ubiquitin binding activity and strong immunoreactivity. Additionally, EgE2D2 and EgE2N were widely distributed in protoscoleces and germinal layer, with differences observed in their distribution in 25-day strobilated worms. Further, these two enzymes were secreted to the hydatid fluid and CE-infected sheep liver tissues via a non-classical secretory pathway. Notably, TGFβ1-induced LX-2 cells exposed to rEgE2D2 and rEgE2N resulted in increasing expression of fibrosis-related genes, enhancing cell proliferation, and facilitating cell migration. Our findings suggest that EgE2D2 and EgE2N could secrete into the liver and may interact with hepatic stellate cells, thereby promoting the formation of liver fibrosis.